2021
DOI: 10.24191/ajue.v17i1.12622
|View full text |Cite
|
Sign up to set email alerts
|

Smart Phone Use among University Students

Abstract: Smartphone users have increased to over two and a half billion people and it is predicted to rise to five billion by the year of 2020. These smartphone users have been spending an increasing amount of time and indicating an obsession with a virtual world. Obviously, smartphone users include students from secondary school to tertiary levels. Their constant engagement with mobile phones has raised questions of whether it has developed into an addiction that may have negative consequences on academic performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
(12 reference statements)
1
12
1
1
Order By: Relevance
“…The study's results are not supported by a Malaysian study that determined smartphone usage among university students and indicated that most students somewhat agreed that they used smartphones without any compelling reasons every hour and that it induced emotional stability [27]. The findings implied that the students were somewhat addicted to smartphones but did not use them for academic purposes.…”
Section: Discussioncontrasting
confidence: 71%
“…The study's results are not supported by a Malaysian study that determined smartphone usage among university students and indicated that most students somewhat agreed that they used smartphones without any compelling reasons every hour and that it induced emotional stability [27]. The findings implied that the students were somewhat addicted to smartphones but did not use them for academic purposes.…”
Section: Discussioncontrasting
confidence: 71%
“…The findings underscored the importance of establishing ethical guidelines for mobile phone use among teachers. Fook et al (2021) explored smartphone usage patterns among university students in Malaysia. Their descriptive study revealed that students exhibited addictive behaviors related to smartphone use, which potentially affected their academic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Penggunaan smartphone dalam pembelajaran matematika dapat mempengaruhi kualitas belajar siswa, terutama jika aplikasi atau materi yang digunakan tidak sesuai dengan kurikulum atau tidak dapat meningkatkan kompetensi siswa (Papadakis et al, 2021); 4) Isolasi: Penggunaan smartphone yang berlebihan dapat menyebabkan siswa menjadi kurang interaktif dalam kelas dan kurang berkoordinasi dengan siswa lain (Fook et al, 2021); 5) Kesehatan: Penggunaan smartphone yang berlebihan dapat menyebabkan masalah kesehatan seperti sakit kepala, kurang tidur, dan gangguan posisi tubuh (Demir & Sümer, 2019); dan 6) Kemampuan berpikir: Penggunaan smartphone yang berlebihan dapat mempengaruhi kemampuan berpikir kritis dan analitis siswa dalam menyelesaikan masalah matematika (Rodríguez et al, 2020).…”
Section: Diskusiunclassified